Konstitusionalisme, Konstitusi Islam dan Perkembangan Konstitusi Indonesia - Boiziardi AS (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
The studies in this research are Constitutionalism, the Islamic Constitution and the Development of the Indonesian Constitution. This research uses normative juridical research. The results of this research explain the philosophical meaning of this understanding of constitutionalism, First, power must be limited, Second, the exercise of power is carried out based on a general agreement which is crystallized in the constitution, and Third, the exercise of power always requires accountability within the framework of the constitution. In the Islamic world, the Medina Charter is known as the constitution for state life. Indonesia has experienced various changes in the constitution.